Instrument Pengukuran Kelelahan pada Pasien HIV - Nugraha, Bambang Aditya; Ramdhanie, Gusgus Ghraha; Sulastini, Sulastini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to identify instruments for measuring fatigue in HIV. The research method used is a narrative review with the criteria for articles published between 2019-2023, complete manuscripts available, and articles using primary data (RCT, cross-sectional, and cohort) in Indonesian and English. The research results showed The Chalder Fatigue Questionnaire (CFQ), Modified Fatigue Impact Scale (MFIS), Fatigue Severity Scale (FSS), Patient-Reported Outcomes Measurement System (PROMIS), HIV-Related Fatigue Scale, Ped-sQL Multidimensional Fatigue Scale (MFS ) and the Functional Assessment of Chronic Illness Therapy Fatigue scale (FACIT-F) are fatigue measurement instruments that can be used in HIV patients. A total of 7 (seven) fatigue measurement instruments were found. The seven instruments have been tested for validity and reliability. In conclusion, nurses can use this instrument to measure fatigue before developing management strategies for people with HIV. Keywords: HIV, Fatigue, Fatigue Measurement